Optimasi Removal Logam Pb Sungai Porong Sidoarjo Terdampak Lumpur Lapindo Menggunakan Biokoagulan Ekstrak Daun Mangga - Asmarani, Nabila Nur Fauziyah Putri; Basri, Moch Faisal; Sabri, Rajib Naji; Hamidah, Laily Noer; Afkar, Khilyatul (2477 - 6165, 2024)
The Lapindo mud is an eruption event caused by excessive soil excavation, leading to contamination in the surrounding area, including the Porong River. Biocoagulants are natural coagulants that can act as flocculants to bind pollutants. This study aims to determine and identify the effectiveness of mango leaves as a biocoagulant in reducing turbidity and heavy metals in the Porong River water. The method used is maceration using ethanol with a concentration of 96% and 70%. The use of different ethanol concentrations creates diverse sample variations. Sample treatment with the biocoagulant involves both rapid and slow stirring. From the results of the study, the maximum reduction of Pb is achieved in variation E using 0.06 ml of 96% ethanol, with 20 minutes of rapid stirring and 40 minutes of slow stirring, resulting in an efficiency of 79.31%. For Cd, the best reduction efficiency is in variation J using 0.06 ml of 70% ethanol, with 15 minutes of rapid stirring and 30 minutes of slow stirring, resulting in an efficiency of 92%. The highest TDS reduction is observed in sample variation F. The findings suggest that mango leaf extract can serve as a natural biocoagulant to reduce the levels of heavy metals in the water of the Porong River.